Normative reference values and regression equations to predict the 6-minute walk distance in the Asian adult population aged 21–80 years - Yeung, Meredith T.; Chan, Melissa Y.; Huang, Katherin S.; Chen, Tian Jie; Chia, Cyprian P.; Fong, Meihiko M.; Ho, Cherilyn S.; Koh, Derek T.; Neo, Mitchell J.; Tan, Mark (Hong Kong physiotherapy journal, 2022)
Summary at a glance: The 6-min walk test (6MWT) is a widely used field walking test. This study reports the normative reference values (NRV) of distance walked during 6MWT (6MWD) in healthy Singaporeans (aged 21–80) and updates the 6MWD reference equations. This information may facilitate the interpretation of the 6MWD in clinical populations. Ethics approval: The Singapore Institute of Technology-Institutional Review Board (SIT-IRB Project Number: 2019099) approved this study to be carried out from June 2019 to January 2021. All participants gave written informed consent before data collection began. Background: The six-minute walk test (6MWT) is a widely adopted submaximal field-walking test to evaluate functional exercise capacity. This validated test is a reliable, safe, inexpensive, and straightforward assessment tool commonly used as an outcome measure, using the distance walked (6MWD) as the primary outcome. An earlier study has established the normative reference values (NRV) and equation in healthy Singaporeans — however, the small sample size and narrow age range curb adequate representation of the adult population profile. Objectives: This study aims to update the NRV and reference equations to predict the distance walked during 6MWT (6MWD) for healthy Singaporeans aged 21–80. Methods: This cross-sectional study recruited community-dwelling healthy subjects aged 21–80 via convenience sampling. Each subject completed two trials of 6MWT according to the standard protocol. Primary outcome measures included 6MWD, pre-and post-test heart rate (HR), oxygen saturation, and blood pressure (BP). Results: 172 healthy Singaporeans ( females = 9 0 , males = 8 2 ) participated. The overall mean 6MWD was 5 7 8 . 0 0 ± 7 5 . 3 8 metres. The age-stratified mean 6MWD ranged from 6 0 1 . 3 ± 7 1 . 7 9 metres (aged 21–39) to 5 1 9 . 0 2 ± 5 5 . 4 2 metres (aged 60–80). Age, gender, and percentage maximum HR predicted (%PredHRmax) were the most significant variables ( p < 0 . 0 0 1 ). 6MWD reference equation = 2 8 8 . 2 8 2 ( height , m ) + 2 7 . 4 6 3 × Gender ( male = 1 ; female = 0 ) + 4 . 3 4 9 ( % predHRmax ) + 1 . 1 9 1 (HR reserve, bpm) − 1 8 5 . 4 3 1 − 1 . 3 4 3 ( age , years ) − 1 . 6 1 4 (weight, kg), R 2 = 5 8 % . Applying equations from other studies to the Singaporean population resulted in an overestimation of the 6MWD. Conclusion: This study updated the NRV and reference equations of 6MWD for healthy Singaporeans aged between 21–80 years. This update revises the local benchmarks of 6MWD in Singapore, a widely adopted outcome measure.